A representação do feminino em A Bela e a Fera: um diálogo entre história, cinema e filosofia - Correia, Ellen Cristina Rodrigues (Universidade do Vale do Rio dos Sinos, 2019)
The aim of the present work is to apprehend, based on the fairy tale cinematographic adaptations to Beauty and the Beast – the french version of 1946 entitled La Belle et la Bête and the american version Beauty and the Beast of 2017 –, female representations and gender roles. To achieve this goal, this paper will analyze filmic works from the perspective of philosophers Simone de Beauvoir with the concept of Another treatise in Judith Butler's book The Second Sex and Gender Performativity in Gender Problems. The methodology used is film analysis with bibliographic reading. Research results show that stereotypes in film productions, as well as other media tools, influence social behaviors. Thus, from the analysis performed, it is clear that there is an evolutionary line of the feminine in the stories represented. This process contemplates changes and permanences in relation to the desired behavioral patterns, functioning as behavioral beacons in Society.
Keywords: Outro; Performatividade de gênero; Análise fílmica; Another; Gender performativity; Film analysis